Poltava State Agrarian Academy EFFECTIVENESS OF LOCAL APPLICATION OF COLLOID OF NANOCLUSTERS AQUACHELATE OF METALS (Ag, Cu, Zn, Mg) IN TREATMENT OF PARODONTOPATHY CONDITIONS IN DOGS - Мірзаєва, М. С. (Scientific Progress & Innovations, 2014)
In work was clear up in dynamics the results of individual morphological indexes of krevicular fluid in comparison under using colloid of nanoclusters akvahelat of metals (Ag, Cu, Zn, Mg) and chlorhexidine digluconate (0,05% solution by the treatment of the early forms of parodontopathy in clinically sick dogs. By ascertainment the comparative effectiveness we were compared: quantitatively and qualitatively dynamics of desquamative pavement epithelium and forms of leukocytes. While topical use of a colloid of nanoclusters recorded gradual normalization of these indexes.